2020
DOI: 10.1016/j.rssm.2020.100508
|View full text |Cite
|
Sign up to set email alerts
|

The “Eye of the Hurricane” Paradox: An Unexpected and Unequal Rise of Well-Being During the Covid-19 Lockdown in France

Abstract: Panel data covering the French population before and after the outbreak of the Covid-19 epidemic reveal that self-reported health and well-being have improved during the lockdown in comparison to previous years. We name this counterintuitive phenomenon the "eye of the hurricane" paradox: the large majority of individuals who are not infected by the virus may be seeing their current condition in a more positive light than they normally would. There are, however, divergences across social groups that reflect soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
110
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(135 citation statements)
references
References 2 publications
(1 reference statement)
14
110
0
3
Order By: Relevance
“…A developing body of research is suggested that for certain groups, there has been an unexpected increase in well-being during COVID-19, known as the 'lockdown paradox'. 18 In France, Pignon and colleagues 6 reported a 54% drop in psychiatric emergency consultations in the first 4 weeks of COVID-19 lockdown, relative to the same period in 2019. The authors cited possible increased strengths and improved coping strategies during disasters as a possible explanation for this phenomenon, 16 as such a trend in mental health presentations was also observed following the September 11 World Trade Centre terrorist attacks.…”
Section: Patient Factorsmentioning
confidence: 99%
“…A developing body of research is suggested that for certain groups, there has been an unexpected increase in well-being during COVID-19, known as the 'lockdown paradox'. 18 In France, Pignon and colleagues 6 reported a 54% drop in psychiatric emergency consultations in the first 4 weeks of COVID-19 lockdown, relative to the same period in 2019. The authors cited possible increased strengths and improved coping strategies during disasters as a possible explanation for this phenomenon, 16 as such a trend in mental health presentations was also observed following the September 11 World Trade Centre terrorist attacks.…”
Section: Patient Factorsmentioning
confidence: 99%
“…While results are mixed, this research has often found relatively high levels of distress. Other studies have involved longitudinal examinations of wellbeing at various stages of the pandemic (e.g., Recchi et al, 2020;Wang et al, 2020). For instance, Recchi et al (2020) examined longitudinal subjective well-being data obtained at four time points from early April to early May 2020 during the early stages of lockdown in France and found no declines in well-being.…”
Section: The Effect Of Pandemic On Well-beingmentioning
confidence: 99%
“…Other studies have involved longitudinal examinations of wellbeing at various stages of the pandemic (e.g., Recchi et al, 2020;Wang et al, 2020). For instance, Recchi et al (2020) examined longitudinal subjective well-being data obtained at four time points from early April to early May 2020 during the early stages of lockdown in France and found no declines in well-being. Nonetheless, these crosssectional and longitudinal studies generally lack a pre-COVID comparison group, which limits meaningful inferences about the causal effect of the pandemic.…”
Section: The Effect Of Pandemic On Well-beingmentioning
confidence: 99%
“…Importantly, women are also more likely to experience mental health problems such as depression and anxiety (Jacobi et al, 2014) and thus are more vulnerable to poorer mental health as a consequence of COVID-19-related stressors (see Pierce et al, 2020 for such findings in the United Kingdom). Others strongly affected by policy measures are those whose employment is insecure, for example, because they are working fewer hours, have been furloughed, or have lost their job; such people experience particularly high stress due to financial insecurity, loss of routine, and social stigma (e.g., during the 2008-2013 financial crisis (Drydakis, 2015); but see also Recchi et al, 2020). Last, people in poor health may be particularly stressed in the current crisis, because the potential health consequences of a COVID-19 infection are likely more severe and they are more likely to be in stricter social and physical isolation (voluntarily, or because of particularly strict rules in institutions such as hospitals).…”
Section: Covid-19 Lockdowns and Mental Healthmentioning
confidence: 99%